Bimbingan Teknis Pembuatan Pakan Ternak Ayam Kampung Berbasis Pakan Lokal di Kelurahan Nambo Kecamatan Nambo Kota Kendari - Sulfitrana, Andini; Nafiu, La Ode; Saili, Takdir; Abadi, Musram; Libriani, Restu; Salido, Wa Laili; Isnaeni, Purnaning Dhian (Vokasi Universitas Halu Oleo, 2020)
The lack of knowledge and skills in preparing domestic chicken rations will affect farmers' incomes. The fact so far shows that commercial animal feed that meets the local market of Southeast Sulawesi comes from outside the Southeast Sulawesi region, particularly South Sulawesi and Java. The price of commercial feed is certainly not cheap and is increasing from year to year, which affects the poor purchasing power of farmers. Improving farmers' knowledge and skills through technical guidance and advice as part of the FPHO Thematic Community Service Program will provide knowledge about the production of domestic chicken feed for farm animals to meet the food needs needed for growth, development and reproduction . This service will run for a month starting June 13, 2020 through July 13, 2020 in Nambo Village, Nambo District, Kendari City. This non-profit activity was carried out with the involvement of the participants in the UHO FPt Thematic KKN. The program is implemented in the form of technical guidance and advice, namely (1) technical guidance and virtual / online advice; and (2) technical guidance and advice using personal methods both individually and over and in compliance with the Covid 19 Prevention Protocol. The material for this Community Service Extension program is the technology for the production of animal feed based on local raw materials. Based on the activities undertaken, the results of FPt UHO's thematic community service will improve farmers 'knowledge and skills in producing local chicken feed based on local raw materials to reduce feed costs and improve farmers' income in Nambo village, Nambo District